2011
DOI: 10.1097/ncq.0b013e3181e4e6dd
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Mislabeled Laboratory Specimens Using Barcode Technology and Bedside Printers

Abstract: Mislabeling of laboratory samples has been found to be a high-risk issue in acute care hospitals. The goal of this study was to decrease mislabeled blood specimens. In the first year after the implementation of a positive patient identification system using barcoding and computer technology, the number of labeling errors decreased from 103 to 8 per year. The outcome was clinically and statistically significant (P < .001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…These could occur due to the unclear or lack of standard procedures in patient identification and sample labelling. Consistently, a previous study [17] has reported that the incidence of labelling errors decreased significantly in the first year followed by replacing barcodes and modern computer technology for patient identification rather old equipments. Other causes of transfusion failures identified by this study included using out-dated techniques for blood sampling, incorrect labelling, loss of correct labels, or failure to check patient identification carefully prior to transfusion [12].…”
Section: Discussionsupporting
confidence: 84%
“…These could occur due to the unclear or lack of standard procedures in patient identification and sample labelling. Consistently, a previous study [17] has reported that the incidence of labelling errors decreased significantly in the first year followed by replacing barcodes and modern computer technology for patient identification rather old equipments. Other causes of transfusion failures identified by this study included using out-dated techniques for blood sampling, incorrect labelling, loss of correct labels, or failure to check patient identification carefully prior to transfusion [12].…”
Section: Discussionsupporting
confidence: 84%
“…These benefits include decreased turnaround time for laboratory test results on specimens other than blood cultures [13]; reduced frequency of misidentified and mislabeled specimens [43,44]; decrease in patient needle-stick bruises; improved quality of specimens; improved working relationships between phlebotomists and nurses; and higher levels of patient satisfaction [42,45]. …”
Section: Discussionmentioning
confidence: 99%
“…Most studies that evaluated this issue in individual laboratories simply cataloged the reasons for rejection, including specimen hemolysis, clotting, mislabeled specimens, and insufficient quantity for test (2,6,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Additionally, a separate body of literature has reported phlebotomy interventions to ameliorate specific acceptability issues, such as techniques to mitigate hemolysis (19)(20)(21) and incorrect labeling (22,23). But there is no widely available framework for helping any given laboratory identify why its own specimens are rejected and target which interventions would be most appropriate.…”
Section: Introductionmentioning
confidence: 99%